Dimensional Engineering Enables 1.31 V Open‐Circuit Voltage for Efficient and Stable Wide‐Bandgap Halide Perovskite Solar Cells. Issue 7 (22nd March 2022) - Yu, Yue; Liu, Rui; Liu, Chang; Hou, Tian; Wu, Qiaofeng; Zhang, Meng; Yu, Hua
Abstract : Wide‐bandgap (WBG) perovskite solar cells (PSCs) are important ingredients for tandem solar cells and play a crucial role in next‐generation multijunction photovoltaics. Yet, the severe open‐circuit voltage loss ( V loss ) and stability have not been solved. Herein, a dimensionally graded 2D/3D heterostructure is fabricated by in situ fabricating a 2D FPEA2 PbI4 capping layer on the surface of the 3D WBG perovskite film. Through this 2D/3D dimensionally graded design, an enhanced build‐in potential promotes the oriented transport of photoinduced carriers and reduces the nonradiative recombination, leading to an ultrahigh open‐circuit voltage of 1.31 V with a minimum V loss of 0.43 V in a 1.74 eV WBG perovskite system and a desirable efficiency of 18.06%. A longer photoluminescence lifetime and decreased trap density indicate the reduced trap‐assisted nonradiative recombination. Moreover, such a 2D/3D heterostructure exhibits enhanced stability under moisture and heat. This passivation strategy offers an effective approach to achieving high open‐circuit voltage WBG PSCs by facile in situ dimensional engineering, which may pave a general way to step forward in achieving high‐performance and stable WBG PSCs. Abstract : A dimensionally graded 2D/3D heterostructure is formed by in situ growing 2D FPEA2 PbI4 perovskite on top of the 3D wide‐bandgap perovskite film, which leads to a high open‐circuitvoltage of 1.31 V with a superior small open‐circuit voltage loss of 0.43 V in a 1.74 eV perovskite solar cell system.